2015
DOI: 10.1103/physreve.92.042127
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions and critical phenomena in the two-dimensional Ising model with dipole interactions: A short-time dynamics study

Abstract: The ferromagnetic Ising model with antiferromagnetic dipole interactions is investigated by means of Monte Carlo simulations, focusing on the characterization of the phase transitions between the tetragonal liquid and stripe of width h phases. The dynamic evolution of the physical observables is analyzed within the short-time regime for 0.5≤δ≤1.3, where δ is the ratio between the short-range exchange and the long-range dipole interaction constants. The obtained results for the interval 0.5≤δ≤1.2 indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…This controversy is a consequence of the limitations introduced by the long-range dipolar interactions on the Monte Carlo simulation results, as will be discussed in the following section. Recently, by using the short-time dynamics approach (STD), Horowitz et al [33] showed that the h 1 -TL transition line presents a continuous character, in agreement with the results obtained by Fonseca et al [32] by studying the complex partition function zeros from multicanonical algorithms. Later, Bab et al studied the h 2 -TL transition line and demonstrated that it is of first order for the 1.2585 δ 1.36 interval and continuous for the 1.37 δ 1.9 interval, with a tricritical point at δ 1.37.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…This controversy is a consequence of the limitations introduced by the long-range dipolar interactions on the Monte Carlo simulation results, as will be discussed in the following section. Recently, by using the short-time dynamics approach (STD), Horowitz et al [33] showed that the h 1 -TL transition line presents a continuous character, in agreement with the results obtained by Fonseca et al [32] by studying the complex partition function zeros from multicanonical algorithms. Later, Bab et al studied the h 2 -TL transition line and demonstrated that it is of first order for the 1.2585 δ 1.36 interval and continuous for the 1.37 δ 1.9 interval, with a tricritical point at δ 1.37.…”
Section: Introductionsupporting
confidence: 70%
“…With an aim to avoid these hindrances, the short-time dynamics approach has already been successfully applied to this model [33,34]. In this method, it is not necessary to have a system in equilibrium, and the simulations proceed within a short-time interval (t mic , t max ).…”
Section: Short-time Dynamics and Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations